2020
DOI: 10.1080/14719037.2020.1718189
|View full text |Cite
|
Sign up to set email alerts
|

Leadership in, of, and for smart cities – case studies from Europe, America, and Australia

Abstract: This paper analyses leadership in, of, and for smart cities. Using a multi-case study research design and Mode 2 research (based upon collaboration between a scholar and a practitioner), we explore smart city initiatives in Europe (Amsterdam, Bristol, and Milton Keynes), North and South America (Chicago and Curitiba), and Australia (Melbourne). We undertake a comparative analysis which looks at leadership through six lenses: place, purpose, person, position, process, and performance. From our analysis four mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 51 publications
(48 reference statements)
0
37
0
Order By: Relevance
“…Research focusing on the investment in IoT, ICTs and cybersecurity policies analyzes the implementation IoT, ICTs and cybersecurity in the city context as well as the consequent advantages (de Falco et al ., 2019; Nesti and Graziano, 2020) and potential problems (Almirall et al , 2016; Taylor Buck and While, 2017) in the implementation of smart city. While IoT and cybersecurity are ubiquitous in society (Li and Liao, 2018; Chatfield and Reddick, 2019) and have an impact on different areas such as governance (Sancino and Hudson, 2020), marketing and communication (Lee and Lee, 2014; Burnes and Towers, 2016), ICTs provide the basis of different strategies of many cities that have joined the smart city trend, as the urbanization process accelerates worldwide to develop new business models for transportation and mobility and improve services (Berrone et al ., 2016). They are used to develop smart city services for actual and potential new citizens and firms, using international marketing and sales strategies focused on the customer view (Lee and Lee, 2014).…”
Section: Thematic View Broad Theme Key Findings and Theoretical Frameworkmentioning
confidence: 99%
“…Research focusing on the investment in IoT, ICTs and cybersecurity policies analyzes the implementation IoT, ICTs and cybersecurity in the city context as well as the consequent advantages (de Falco et al ., 2019; Nesti and Graziano, 2020) and potential problems (Almirall et al , 2016; Taylor Buck and While, 2017) in the implementation of smart city. While IoT and cybersecurity are ubiquitous in society (Li and Liao, 2018; Chatfield and Reddick, 2019) and have an impact on different areas such as governance (Sancino and Hudson, 2020), marketing and communication (Lee and Lee, 2014; Burnes and Towers, 2016), ICTs provide the basis of different strategies of many cities that have joined the smart city trend, as the urbanization process accelerates worldwide to develop new business models for transportation and mobility and improve services (Berrone et al ., 2016). They are used to develop smart city services for actual and potential new citizens and firms, using international marketing and sales strategies focused on the customer view (Lee and Lee, 2014).…”
Section: Thematic View Broad Theme Key Findings and Theoretical Frameworkmentioning
confidence: 99%
“…Based on the five definitions of the smart city concept mentioned in session 1, and taking into account the conceptual framework of Figure 1, future work could expand the discussions in the proposed study areas. For example, one of the definitions that needs to be expanded is the u-City concept, to know the impact generated by the advances of the AI application areas in social development, from a perspective framed in human and social capital [14][15][16].…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…The extensive review of the literature on smart cities conducted by Meijer and Bolivar (2016) reveal three common foci that are dominant in extant smart city research, namely, technological focus, human resource focus and governance focus. An international comparative study found that from a leadership perspective, smart cities can be seen as digital government, a digital driver for economic growth, an open platform for digital socio-political innovation, and an open platform for the digital economy (Sancino and Hudson, 2020). For the purpose of this study, we take an integrative approach to the concept of smart cities and view and discuss it from economic, political, social and cultural perspectives.…”
Section: Linking Coworking Spaces To Smart City Ecosystemsmentioning
confidence: 99%